2020
DOI: 10.3390/catal10050545
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ga2O3 and TiO2 Nanostructures for Photocatalytic Degradation of Volatile Organic Compounds

Abstract: The photocatalytic degradation of formaldehyde, acetaldehyde, toluene, and styrene are compared using monoclinic Ga2O3 and anatase TiO2 nanostructures under ultraviolet-C irradiation. These Ga2O3 and TiO2 photocatalysts are characterized using a field emission scanning electron microscope, a powder X-ray diffraction system, the Brunauer–Emmett–Teller method, and a Fourier transform infrared spectrometer. The Ga2O3 shows a higher reaction rate constant (k, min−1) than TiO2 by a factor of 7.1 for toluene, 8.1 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…9-12 b-Ga 2 O 3 has a high redox potential, which is benecial for photocatalytic reactions under photoexcitation conditions. 9,13 Its redox potential is higher than TiO 2 , so it exhibits better photocatalytic performance than conventional TiO 2 photocatalysts. Meanwhile, the recombination of photogenerated electron-hole pairs is known to severely degrade photocatalytic efficiency; 14,15 when the electron-hole pairs recombine and the carrier concentrations become depleted, the photocatalytic reactions decrease as a consequence.…”
Section: Introductionmentioning
confidence: 99%
“…9-12 b-Ga 2 O 3 has a high redox potential, which is benecial for photocatalytic reactions under photoexcitation conditions. 9,13 Its redox potential is higher than TiO 2 , so it exhibits better photocatalytic performance than conventional TiO 2 photocatalysts. Meanwhile, the recombination of photogenerated electron-hole pairs is known to severely degrade photocatalytic efficiency; 14,15 when the electron-hole pairs recombine and the carrier concentrations become depleted, the photocatalytic reactions decrease as a consequence.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 a shows the pseudo-first-order kinetics of the MB reduction with different TEOA concentrations (0–15 wt.%). For comparison, the M0 and T0 were also included as a control set of experiments because the MB itself could be slightly reduced upon UVC exposure [ 16 ]. Table 1 includes the specific sample notation for the different TEOA concentrations, along with the linear regression coefficient (coefficient of determination, R 2 ) obtained from Figure 2 a.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical reduction of the MB solution can be initiated by catalysts such as the Ga 2 O 3 photocatalyst [ 15 ]. The Ga 2 O 3 nanoparticle was in the form of nanorods whose average length was about 3 μm and whose surface area was 32.2 m 2 /g using the Brunauer–Emmett–Teller (BET) method [ 16 ]. The degree of the color change in the MB solution can be used as an indicator of UVC exposure, and in this work, we used the MB reduction rate (MBR) as a numerical indicator of the UVC exposure.…”
Section: Methodsmentioning
confidence: 99%
“…The photogenerated charge carriers then travel to the surface of β-Ga 2 O 3 where they take part in redox reactions [22,23]. The basic mechanism of photocatalytic decomposition is derived from the oxidation of organisms to H 2 O, CO 2 along with -OH or O 2 radicals produced on the surface of β-Ga 2 O 3 under UCV irradiation [2,8]. In the heterogeneous reaction system, Ga 2 O 3 is excited by the photon energy more so than the band gap energy.…”
Section: Resultsmentioning
confidence: 99%
“…Gallium oxide (Ga 2 O 3 ) has recently been considered as an attractive alternative due to its long stability and high redox capabilities [6,7]. Yoo et al demonstrated a superior photocatalytic activity of Ga 2 O 3 on VOCs compared to that of TiO 2 [8]. In particular, monoclinic gallium oxide (β-Ga 2 O 3 ) has emerged because of its wide bandgap (4.7-4.9 eV) and unique optical properties [9].…”
Section: Introductionmentioning
confidence: 99%